Optimization of Lattice Parameters for Selective Laser Melting Process using DOE-FEM Approach - Using, Meryl Shasha; Ibrahim, Mohd Halim Irwan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
One of the highly promising and advanced Additive Manufacturing (AM) methods capable of directly fabricating functional metallic parts is Selective Laser Melting (SLM). SLM, a type of Laser Powder Bed Fusion (LPBF) AM, involves creating metallic components from CAD data by layer-by-layer fusion of metallic powders using a laser energy source, resulting in the production of 3D metal materials. Lattice parameters such as unit cell size, cell thickness, and solid wall thickness were studied by utilizing a numerical-based design of experiment (DOE-FEM) approach to plan and conduct the experiment systematically with the goal of gaining optimal lattice parameters for the application of metallic lattice components. This study simulates a Ti-6Al-4V rectangular block with a gyroid lattice structure, aiming to analyse and compare results residual stress and distortion between DOE combinations and an optimized lattice parameter. The lattice structure is generated using nTopology software, and the SLM simulation is carried out with various input parameters using Simufact Additive software to analyse the impact on the lattice structure and final product. The optimization of lattice parameters in the SLM process is performed through a numerical simulation using a DOE-FEM approach with Minitab software. These findings provide valuable insights into the behaviour of Ti-6Al-4V gyroid lattice structures and highlight the importance of considering lattice parameters, including overall dimensions, when designing standard specimens to analyse residual stress and distortion.